PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS INKUIRI TERBIMBING PADA MATERI FLUIDA STATIS - Febrizha, Sofya; Maharta, Nengah; Ertikanto, Chandra (Jurnal Pembelajaran Fisika, 2015)
This research was aimed to develop a product in the form of guided inquiry-based student worksheet on the material of static fluid, and to describe the attractiveness, easiness, the benefit of using product, and the effectiveness of the product. The development included the potential and problems, Â data collection, product design, design validation, revision design, product test, product revision, utiliy trial and production. The product of development result was the guided inquiry-based student worksheet. It was validated with the attractivenes score of 3,28 (very attractive), the easiness score of 3,33 (very easy), the benefit score of 3,19 (useful). The effectiveness level of the student worksheet was at approximately 80.00% of student reaching the minimal score of completeness (KKM). Therefore, the student worksheet is effectively used as a medium of learning.Penelitian ini bertujuan menghasilkan produk berupa LKS berbasis inkuiri terbimbing pada materi fluida statis, serta mendeskripsikan kemenarikan, kemudahan, kemanfaatan, dan keefektifan produk. Pengembangan tersebut meliputi potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain, uji coba produk, revisi produk, uji coba pemakaian,dan produksi. Hasil pengembangan menghasilkan LKS berbasis inkuiri terbimbing. Produk akhir sudah valid dalam aspek kemenarikan dengan skor 3,28 (sangat menarik), untuk Â aspek kemudahan dengan skor 3,33 (sangat mudah), aspek kemanfaatan dengan skor 3,19 (bermanfaat). Tingkat keefektifan LKS berbasis inkuiri terbimbing pada materi fluida statis yaitu sebanyak 80,00% siswa telah mencapai KKM. Sehingga LKS dikatakan efektif digunakan sebagai salah satu media pembelajaran.Kata kunci: fluida statis, inkuiri terbimbing, LKS, media pembelajaran.